2007
DOI: 10.1177/0272989x07309642
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Incomparable? A Systematic Review of Competing Techniques for Converting Descriptive Measures of Health Status into QALY-Weights

Abstract: Despite the recent proliferation of conversion algorithms, a number of questions bearing on the derivation and interpretation of derived QALY-weights remain unresolved. These unresolved issues suggest directions for future research in this area. In the meantime, analysts seeking guidance in selecting derived QALY-weights should consider the validity and feasibility of each conversion algorithm in the disease area and patient group under evaluation rather than restricting their choice to weights from a particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
149
0
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(157 citation statements)
references
References 61 publications
3
149
0
5
Order By: Relevance
“…In a review of crosswalk studies and methodology, Mortimer and Segal [8] addressed the methodological and conceptual concerns with regression crosswalk methodology and found large variation in the explanatory power of regression models. A broad overview of study results indicates that the explanatory power of the regression models is lower when converting scores with disparate constructs and measurement scales [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a review of crosswalk studies and methodology, Mortimer and Segal [8] addressed the methodological and conceptual concerns with regression crosswalk methodology and found large variation in the explanatory power of regression models. A broad overview of study results indicates that the explanatory power of the regression models is lower when converting scores with disparate constructs and measurement scales [6].…”
Section: Discussionmentioning
confidence: 99%
“…Much of this type of mapping, or crosswalk, methodology has been previously conducted using other outcome measurement tools with the purpose of predicting a generic, preference-based healthy utility measure from a diseasespecific measure or two generic health-related quality-of-life instruments [2,4,8]. To our knowledge, there are no equivalent studies in arthroplasty that offer a direct comparison to our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Head-to-head comparisons were identified in 392 studies, suggesting low level of agreement, and hence a need for developing algorithms to compare utility scores across the various instruments used. Crosswalks or 'mappings' between a disease specific instrument and a HSU-instruments are commonly used to enable QALY estimations [6,7]. However, while such crosswalks between HSU-instruments are rare [8][9][10][11], previous studies have indicated non-linear relationships [8,9,11].…”
Section: Introductionmentioning
confidence: 99%
“…Mortimer and Segal [7] aimed to compare four methods for estimating QALY weights from non-PBMs, including derivation of a PBM from an existing measure, and to determine what effect the choice of method may have on the values generated. Their review included generic and conditionspecific measures.…”
mentioning
confidence: 99%